SURGICAL TREATMENT OF PATIENTS WITH LOCALLY ADVANCED TONGUE CANCER AND CANCER OF ORAL CAVITY - P. V. Svetitsky; M. V. Bauzhadze (Креативная хирургия и онкология, 2017)
The method of operation at locally-advanced tongue cancer and cancer of oral cavity is presented. The operation has  been  performed in 20  patients. The method allows  to  preserve tongue function without its deformation and  falling back,  improves  life quality,  restores natural breathing, swallowing  and speech. By the end of 24 months survival in free  period was observed in 43,8±11,0% patients, total survival – 56.3±10,0% patients.